The development of a consensus definition for healthcare improvement science (HIS) in seven European countries - Skela-Savič, Brigita (Zdravstveno varstvo, 2017)
Introduction. There is a limited body of research in the field of healthcare improvement science (HIS). Quality improvement and %change making% should become an intrinsic part of everyone%s job, every day in all parts of the healthcare system. The lack of theoretical grounding may partly explain the minimal transfer of health research into health policy. Methods. This article seeks to present the development of the definition for healthcare improvement science. A consensus method approach was adopted with a two-stage Delphi process, expert panel and consensus group techniques. A total of 18 participants were involved in the expert panel and consensus group, and 153 answers were analysed as a part of the Delphi survey. Participants were researchers, educators and healthcare professionals from Scotland, Slovenia, Spain, Italy, England, Poland, and Romania. Results. A high level of consensus was achieved for the broad definition in the 2nd Delphi iteration (86%). The final definition was agreed on by the consensus group: %Healthcare improvement science is the generation of knowledge to cultivate change and deliver person-centred care that is safe, effective, efficient, equitable and timely. It improves patient outcomes, health system performance and population health.% Conclusions. The process of developing a consensus definition revealed different understandings of healthcare improvement science between the participants. Having a shared consensus definition of healthcare improvement science is an important step forward, bringing about a common understanding in order to advance the professional education and practice of healthcare improvement science.
Keywords: consensus methods; definicija; definition; Europe; Evropa; health care; healthcare; HIS; improvements; izboljšave; metode konsenza; science; zdravstvo; znanost; znanost o uvajanju izboljšav v zdravstvu